2023
DOI: 10.3390/foods12030646
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Future of Insects in the European Food System: A Systematic Review Based on the Consumer Point of View

Abstract: Edible insects recently gained attention as a potential contributor to the future sustainability of the food system. Insect farming has indeed shown to have environmental and nutritional benefits, but edible insects are still an unusual foodstuff in Europe. The purpose of this article is to analyze the barriers and drivers of insect consumption in Europe and to identify the most promising strategies to convince consumers to include insect-based products in their diets. To answer these research questions, a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…There are two distinct psychological responses to eating insects: In civilizations where entomophagy is common, insects are appreciated as a source of nutrients; nevertheless, in Western cultures, they are viewed as filthy, revolting, and potentially harmful (Baiano, 2020). Experience and familiarity are other drivers that often influence EIs consumption (Mina & Peira, 2023). The knowledge of entomophagy, as determined by prior knowledge or previous insect ingestion, and the experiences gained from eating insects might significantly increase people's acceptance of them.…”
Section: Factors Affecting Consumer Acceptability Of Edible Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two distinct psychological responses to eating insects: In civilizations where entomophagy is common, insects are appreciated as a source of nutrients; nevertheless, in Western cultures, they are viewed as filthy, revolting, and potentially harmful (Baiano, 2020). Experience and familiarity are other drivers that often influence EIs consumption (Mina & Peira, 2023). The knowledge of entomophagy, as determined by prior knowledge or previous insect ingestion, and the experiences gained from eating insects might significantly increase people's acceptance of them.…”
Section: Factors Affecting Consumer Acceptability Of Edible Insectsmentioning
confidence: 99%
“…Hands‐on experiences can help people overcome their aversion and build confidence in trying and cooking with insects. It is possible to approach and entice people to try insects for the first time by expanding the number of occasions when these items can be tried, making them readily available on the shelves of supermarkets and restaurants, and including them in well‐known cookery programs (Mina & Peira, 2023). It is worth noting that introducing any new food item requires time, patience, and open‐mindedness.…”
Section: Nine Strategies To Enhance Consumers’ Acceptability Of Edibl...mentioning
confidence: 99%
“…A systematic review of 91 studies found that, among several meat substitutes, insects were the least accepted 32 . Many studies show a very low willingness among consumers to try insect-based products, generally below 30 percent, although higher percentages sometimes emerge in the literature 33 . In the UK, the inclination to consume insects is similarly low, with only about 24 percent of consumers showing a willingness to do so 34 .…”
Section: Consumer Acceptance Of Insects As Foodmentioning
confidence: 99%
“…The main barrier to market development in Western countries is the "psychological rejection experienced by consumers", predominantly due to feelings of disgust 33,34,[36][37][38][39][40] . Disgust, a response of revulsion or strong disapproval to something perceived as unpleasant or offensive 41 , serves as an emotional defence mechanism to avoid ingesting potentially harmful substances through the mouth 42 .…”
Section: Disgustmentioning
confidence: 99%
“…While the variety of edible insects is vast, every country and region have rigorous legal restrictions in place concerning the utilization, processing, and commercialization of such insects in human food and animal feed (Montowska et al., 2019; Borges et al., 2022; Żuk‐Gołaszewska et al., 2022). It is worthy to note that on February 10, 2022, the Commission Implementing Regulation (EU) 2022/188 was enacted, which permits the commercialization of frozen, dried, and powdered variants of Acheta domesticus , the house cricket, as a Novel Food in accordance with Regulation (EU) 2015/2283 of the European Parliament and of the Council (Żuk‐Gołaszewska et al., 2022; Mina et al., 2023). Therefore, house cricket, A. domesticus , is the third approved insect following yellow meal worm ( Tenebrio molitor ) and migratory locust ( Locusta migratoria ) (Formici, 2022).…”
Section: Introductionmentioning
confidence: 99%